Melville, Whitman, and metonymy: towards a new poetics of community. Issue 10 (26th November 2019) - Claviez, Thomas
ABSTRACT: Melville's enigmatic short story 'Bartleby, the Scrivener', has puzzled critics and readers alike ever since its publication in 1853. It has, however, recently received an even more puzzling amount of critical attention by the likes of Gilles Deleuze, Giorgio Agamben, Slavoj Žižek, and Jacques Rancière. The essay argues that the approaches of the latter have to be considered in the light of what can be termed a 'metonymic poetics of community'. Read in this way, the hermetic figure of the copyist can be juxtaposed to Walt Whitman's notorious lists, as that which cannot be integrated into the omnivorous, imperial I/eye of the poet laureate of American democracy; as that which defies being sublated into a metaphoric conception of community.